2019
DOI: 10.2147/ott.s217528
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resection as first-line therapy for large hepatic sclerosing hemangioma: a case report</p>

Abstract: Hepatic sclerosing hemangioma is a rare benign disease that occurs in association with hepatic cavernous hemangioma degeneration and sclerosis. Recent studies have shown that radiofrequency (RF) ablation is an alternative treatment for hepatic cavernous hemangiomas, even for large hemangiomas (≥10 cm). However, RF ablation might not be suitable to treat large sclerosing hemangiomas. We herein report the successful surgical removal of a large hepatic sclerosing hemangioma after RF ablation treatment failure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous case reports have indicated that most patients with this condition exhibit ring enhancement on CT scans, while MRI images lack specificity, often leading to misdiagnosis as liver malignancies, such as metastases, hepatocellular carcinoma, and cholangiocarcinoma, during preoperative assessments (Table1). [5][6][7][8][9][10][11][12][13] Notably, serological indicators and tumor markers typically fall within the normal range for most patients with sclerosing hemangioma. Hence, clinicians must exercise caution when diagnosing cases with ambiguous imaging features and normal tumor-related indexes, considering the inclusion of rare benign liver tumors into the identification of liver malignant tumors, such as hepatic sclerosing hemangioma, in the differential diagnosis of liver malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports have indicated that most patients with this condition exhibit ring enhancement on CT scans, while MRI images lack specificity, often leading to misdiagnosis as liver malignancies, such as metastases, hepatocellular carcinoma, and cholangiocarcinoma, during preoperative assessments (Table1). [5][6][7][8][9][10][11][12][13] Notably, serological indicators and tumor markers typically fall within the normal range for most patients with sclerosing hemangioma. Hence, clinicians must exercise caution when diagnosing cases with ambiguous imaging features and normal tumor-related indexes, considering the inclusion of rare benign liver tumors into the identification of liver malignant tumors, such as hepatic sclerosing hemangioma, in the differential diagnosis of liver malignancies.…”
Section: Discussionmentioning
confidence: 99%